2020
DOI: 10.18632/aging.103630
|View full text |Cite
|
Sign up to set email alerts
|

Distant metastasis prediction via a multi-feature fusion model in breast cancer

Abstract: This study aimed to develop a model that fused multiple features (multi-feature fusion model) for predicting metachronous distant metastasis (DM) in breast cancer (BC) based on clinicopathological characteristics and magnetic resonance imaging (MRI). A nomogram based on clinicopathological features (clinicopathological-feature model) and a nomogram based on the multi-feature fusion model were constructed based on BC patients with DM (n=67) and matched patients (n=134) without DM. DM was diagnosed on average (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 19 publications
(19 reference statements)
0
18
0
Order By: Relevance
“…Wang et al [18] found that the rate of disease-free survival at 5 years was 73.3% among BRCA mutation carriers, as compared with 91.1% among non-carriers. Previous studies demonstrated that some factors including tumour size, multiple masses, fat-saturated T 2 WI signal, were con rmed to be associated with distant metastasis [25][26] . Some independent clinicopathologic factors were previously con rmed to be associated with distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [18] found that the rate of disease-free survival at 5 years was 73.3% among BRCA mutation carriers, as compared with 91.1% among non-carriers. Previous studies demonstrated that some factors including tumour size, multiple masses, fat-saturated T 2 WI signal, were con rmed to be associated with distant metastasis [25][26] . Some independent clinicopathologic factors were previously con rmed to be associated with distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the definition of BM (SBM/MBM) was a global concern in distant metastasis [ 26 , 27 ]. Sufficient evidence showed the significant difference between SBM and MBM in clinicopathologic characteristics and survival outcome [ 21 , 26 , 28 ]. However, SBM and MBM were still not well defined, which might be the main reason for inconsistent conclusions in previous studies [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer antigen 15-3 (CA15-3) in addition to carcinoembryonic antigen (CEA) along with cancer antigen 125 (CA125) are extensively used in the clinical practice of breast cancer as serum tumor markers. These have been developed as noninvasive, easily available, and cost-effective tumor markers for immediate diagnosis, monitoring, and prediction of breast cancer [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%